Baby senses - " Miriam " (2007)
Baby Senses: A Sensory Neuroscience Primer for All Ages" is an educational book by Dr. Jaya Viswanathan that explores the diverse sensory systems across the animal kingdom. The book delves into sixteen sensory systems, extending beyond the traditional five human senses to include internal sensory mechanisms and unique abilities like detecting electrical and magnetic fields.